KEARIFAN LOKAL DAN UPAYA PELESTARIAN LINGKUNGAN AIR: STUDI ETNOGRAFI MASYARAKAT ADAT MANGGARAI, FLORES, NUSA TENGGARA TIMUR - Niman, Erna Mena; Tapung, Marianus mantovani; Ntelok, Zepisius Rudiyanto Eso; Darong, Hieronimus Canggung, - (Paradigma: Jurnal Kajian Budaya, 2023)
The efforts and conservation actions are needed to obtain a clean water for consumption. One of such efforts is interpreting the traditions of indigenous peoples, which are directly related to the concept of nature conservation. This study aims to identify and describe the meaning and geographical aspects of the barong wae ritual practice of the Manggarai indigenous people in the context of preserving the water environment. This research was a qualitative descriptive study with an ethnographic approach. Data were collected through in-depth interviews, participatory observation, and documentation. Results show that local wisdom in the form of the barong wae ritual contains knowledge, ethics, values, and norms that are directly related to the efforts to protect the water environment. This is reflected in the meaning of the symbols, the selection of locations, and the involvement of indigenous peoples as a form and means of human interaction with the environment, especially the water environment. In conclusion, local cultural values, ethics, moral standards, and norms embodied in symbols, locations, and community involvement in the implementation of barong wae cultural rites must be preserved for the survival and sustainability of the natural environment, especially the water environment, for the next generation.